Motivations, acceptability and ethical considerations for interventional HIV cure research at the end of life: perspectives from long-term survivors of HIV in the United States - Ali Ahmed; Jeff Taylor; Whitney Tran; Simran Swaitch; Samuel O. Ndukwe; Rachel Lau; Kris H. Oliveira; Stephanie Solso; Cheryl Dullano; Andy Kaytes; Davey Smith; Robert Deiss; et al. (BMC Medical Ethics)
Abstract Introduction Despite progress in antiretroviral therapy (ART), an effective cure for HIV remains out of reach. End-of-life (EOL) research studies involving individuals with a prognosis of six months or less offers an opportunity to advance cure science but has so far been limited to observational designs focused on HIV reservoirs. As interventional approaches at the EOL are now being considered, it is essential to assess their acceptability before moving forward. Understanding how long-term survivors (LTS) of HIV perceive these potential interventions, along with their motivations and ethical considerations, is critical to guiding the design of future EOL-HIV interventional research. Methods We conducted in-depth qualitative interviews with 16 LTS of HIV from across regions in United States to examine their views on hypothetical interventional HIV cure research at the EOL. To ensure representation, we recruited participants through community-based organizations and HIV cure collaboratories using purposive-sampling. We conducted interviews via secure teleconferencing, transcribed the recordings, and used inductive thematic analysis to identify key themes related to motivations, acceptability, and ethical considerations surrounding interventional EOL HIV cure research. Results Participants viewed hypothetical interventional HIV cure research at the EOL as a way to contribute to science, despite expecting no personal benefit. They prioritized autonomy and informed-choice in ethical participation. Many supported latency-reversing agents but raised safety concerns; in contrast, they viewed block-and-lock strategies as promising and less risky. Participants generally welcomed immune-based approaches, though some questioned their suitability for older adults near the EOL. LTS found cell and gene-based interventions innovative but expressed caution about safety and feasibility. While they valued the scientific potential of combination strategies, they noted their complexity and burden. Opinions on analytical treatment interruptions were mixed and depended on ethical safeguards, including medical oversight and reversibility. Willingness to participate in hypothetical HIV cure research at the EOL reflected individual health status, perceived burden, and personal values. Conclusions LTS are willing to engage in interventional EOL HIV cure research but emphasize the importance of ethical safeguards and participant autonomy. As HIV cure research progresses, integrating LTS perspectives is critical to designing feasible, ethical, and scientifically impactful interventional studies at EOL.